Electrostatic Effects on the Population of Atropisomers of Charged and Dipolar Derivatives of 1,8-Di(2‘-pyridyl)naphthalene - Zoltewicz, John A; Maier, Nobert M; Fabian, Walter M. F (Journal of organic chemistry, 1997)
Dicationic 1‘,1‘-dimethyl (6a), dipolar 1‘,1‘-dioxide (6b), and 6‘,6‘-dipyridone (7) derivatives of 1,8-di(2‘-pyridyl)naphthalene were prepared. Proton NMR failed to reveal the presence of individual anti-syn atropisomers over a wide range of temperatures. By contrast, the 1‘,1‘‘-dimethyl derivative of 1-(2‘-pyridyl)-8-(3‘‘-pyridyl)naphthalene (8), a positional isomer of 6a, existed in DMSO-d 6 as a 2:1 mixture of anti to syn atropisomers at ambient temperatures. Electrostatic repulsion is believed to cause the anti atropisomer to be favored, especially in 6a where the charged regions are closer together than in 8, owing to the splayed-out arrangement of the rings. AM1 and PM3 computations confirm that the anti is highly favored over the syn isomer for 6a, 6b, and 7.